The Antibody Receptor Fc Gamma Receptor IIIb Induces Calcium Entry via Transient Receptor Potential Melastatin 2 in Human Neutrophils - Alemán, Omar Rafael; Mora, Nancy; Rosales, Carlos (Frontiers in Immunology, 2021)
Human neutrophils express two unique antibody receptors for IgG, the FcγRIIa and the FcγRIIIb. FcγRIIa contains an immunoreceptor tyrosine-based activation motif (ITAM) sequence within its cytoplasmic tail, which is important for initiating signaling. In contrast, FcγRIIIb is a glycosylphosphatidylinositol (GPI)-linked receptor with no cytoplasmic tail. Although, the initial signaling mechanism for FcγRIIIb remains unknown, it is clear that both receptors are capable of initiating distinct neutrophil cellular functions. For example, FcγRIIa is known to induce an increase in L-selectin expression and efficient phagocytosis, while FcγRIIIb does not promote these responses. In contrast, FcγRIIIb has been reported to induce actin polymerization, activation of β1 integrins, and formation of neutrophils extracellular traps (NET) much more efficiently than FcγRIIa. Another function where these receptors seem to act differently is the increase of cytoplasmic calcium concentration. It has been known for a long time that FcγRIIa induces production of inositol triphosphate (IP3) to release calcium from intracellular stores, while FcγRIIIb does not use this phospholipid. Thus, the mechanism for FcγRIIIb-mediated calcium rise remains unknown. Transient Receptor Potential Melastatin 2 (TRPM2) is a calcium permeable channel expressed in many cell types including vascular smooth cells, endothelial cells and leukocytes. TRPM2 can be activated by protein kinase C (PKC) and by oxidative stress. Because we previously found that FcγRIIIb stimulation leading to NET formation involves PKC activation and reactive oxygen species (ROS) production, in this report we explored whether TRPM2 is activated via FcγRIIIb and mediates calcium rise in human neutrophils. Calcium rise was monitored after Fcγ receptors were stimulated by specific monoclonal antibodies in Fura-2-loaded neutrophils. The bacterial peptide fMLF and FcγRIIa induced a calcium rise coming initially from internal pools. In contrast, FcγRIIIb caused a calcium rise by mobilizing only extracellular calcium. In addition, in the presence of 2-aminoethoxydiphenyl borate (2-APB), an inhibitor of TRPM2, FcγRIIIb-induced calcium rise was blocked. fMLF- or FcγRIIa-induced calcium rise was not affected by 2-APB. These data suggest for the first time that FcγRIIIb aggregation activates TRPM2, to induce an increase in cytoplasmic calcium concentration through calcium internalization in human neutrophils.